Global population aging: Unequal distribution of risks in later life between developed and developing countries. (August 2015) - Higo, Masa; Khan, Hafiz TA
Much of the existing research on population aging has focused on its impact, including both opportunities and challenges, on developed countries, particularly those in Europe and North America. This article discusses how unequally population aging will distribute risks in securing socio-economic resources for the wellbeing of individuals in later life between developed and developing countries around the world. Based on a documentary analysis of relevant literature and findings from the survey data drawn from Organization for Economic Co-operation and Development (OECD), United Nations (UN), and World Health Organization (WHO), this article discusses four main areas of the unequal distribution of risks in later life: (1) burden of disease in epidemiological transition, (2) financial security in retirement, (3) familial resources for elderly care, and (4) care workforce for elderly care. While population aging is a global trend, its impact is not equal; over the next decades, today's developing countries will likely contend with double challenges at least in these areas.